3D printed nutritious snacks from orange peel waste. (2022) - Leo, Chen Huei; Lee, Cheng Pau; Foo, Su Yi; Tan, Joseph Choon Wee; Tan, Jian Da; Ong, Eng Shi; Hashimoto, Michinao
Abstract: The discarded section of an orange fruit, orange peel waste (OPW), is well-recognised as a rich source of vitamins and nutrients that can be turned into high-value-added food products. OPW is produced in millions of tonnes over the world and returned to the environment with little benefit. As a result, there is an urgent need to develop better methods to effectively upcycle the industry's enormous volume of OPW produced yearly. Recent advances in 3D printing technology have enabled food to be created into unique and complex 3D structures with potential benefits to health and environment. Thus, the objective of this research is to develop a method to upcycle OPW into healthy snacks using 3D printing technology such as direct ink writing (DIW). Using DIW 3D printing, an edible 3D structures of orange peels using rheology-modified inks containing OPW was successfully fabricated. Furthermore, OPW also contains bioflavonoids and exhibit antioxidant activity. Therefore, this study provided an example of a feasible method to upcycle food waste into high value food products, which pave an avenue to achieve food sustainability and circularity of food waste management using 3D food printing as a technological vehicle.